2005
DOI: 10.1111/j.1365-2893.2005.00682.x
|View full text |Cite
|
Sign up to set email alerts
|

Black patients with chronic hepatitis C have a lower sustained viral response rate than non‐Blacks with genotype 1, but the same with genotypes 2/3, and this is not explained by more frequent dose reductions of interferon and ribavirin*

Abstract: In previous hepatitis C virus (HCV) treatment studies, Black patients not only had a lower sustained viral response (SVR) rate to interferon and ribavirin (RBV) than non-Black patients but also a higher frequency of HCV genotype 1 (GT-1) infection. The aim of this community-based study was to determine whether Black patients have a lower SVR rate independent of genotype. We prospectively enrolled 785 patients (24.8% Black, 71.5% White, 3.7% others) who received interferon alpha-2b 3 MU three times weekly + RBV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
1
40
0
Order By: Relevance
“…[4][5][6]16 Our results confirm studies that found that African Americans had significantly lower SVR rates than did whites [17][18][19] and that patients who had not responded to a prior course of nonpegylated interferon also had a lower SVR rate. 20 Our finding of a decreased SVR rate among patients with diabetes supports recent work indicating that insulin resistance impairs the response to PEG-INF/ ribavirin.…”
Section: Discussionsupporting
confidence: 80%
“…[4][5][6]16 Our results confirm studies that found that African Americans had significantly lower SVR rates than did whites [17][18][19] and that patients who had not responded to a prior course of nonpegylated interferon also had a lower SVR rate. 20 Our finding of a decreased SVR rate among patients with diabetes supports recent work indicating that insulin resistance impairs the response to PEG-INF/ ribavirin.…”
Section: Discussionsupporting
confidence: 80%
“…Because low treatment rates in African American patients may be explained by the high prevalence of genotype-1 HCV, we also entered an interaction term between race and genotype in the model. 29 Provider factors included provider type, clinical experience, and continuity of primary care. We identified provider type based on the clinics where PCP (clinic codes 323, 322, 348, 350) and specialists (clinic codes 307, 454) provided care for the study cohort.…”
Section: Predictorsmentioning
confidence: 99%
“…African Americans (AA) are infected with HCV genotype 1 at a much higher rate than Caucasian Americans (CA) (91% vs. 70%, respectively) (4), and SVR rates are lower in AA (19-28%) compared to CA (39-52%) (9)(10)(11). These racial differences are not likely explained by differences in frequency of ribavirin dose reductions or PEGIFN systemic exposure (12,13). Although IL-28B polymorphism is a known predictor of SVR, the interaction between ribavirin exposure, race, IL-28B genotypes (CC, CT, and TT), and SVR has not been fully explored.…”
Section: Introductionmentioning
confidence: 96%